2020
DOI: 10.26719/emhj.19.018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knowledge and skill for basic life support in personnel of emergency medical services, Islamic Republic of Iran

Abstract: Background: Considering the importance of pre-hospital resuscitation, it is necessary to update staff on the relevant knowledge and skills through education, sufficient practice, good supervision and recruitment of appropriately qualified cadres. Aims: This study aimed to determine the association between knowledge and skills for emergency medical services (EMS) of basic life support in northwest Khuzestan province, Islamic Republic of Iran, in 2016. Methods: This cross-sectional study was conducted on all EMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
2
7
2
Order By: Relevance
“…Several other studies also reported that training in the last 3 or 6 months significantly increased the level of CPR knowledge [ 15 19 ]. In a systematic review where 34 different studies were evaluated, it was determined that, regardless of the time of training, people who had received CPR training at some point had significantly higher levels of CPR skills compared to those who had never received it [ 20 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several other studies also reported that training in the last 3 or 6 months significantly increased the level of CPR knowledge [ 15 19 ]. In a systematic review where 34 different studies were evaluated, it was determined that, regardless of the time of training, people who had received CPR training at some point had significantly higher levels of CPR skills compared to those who had never received it [ 20 ].…”
Section: Discussionmentioning
confidence: 90%
“…This study examined the level of knowledge among EMTs and paramedics working in Kayseri 112 emergency health system regarding CPR. It was determined that having received training on CPR after 2015, having participated in a course or seminar on CPR in the last 3 months and having practiced defibrillation/ Several other studies also reported that training in the last 3 or 6 months significantly increased the level of CPR knowledge [15][16][17][18][19]. In a systematic review where 34 different studies were evaluated, it was determined that, regardless of the time of training, people who had received CPR training at some point had significantly higher levels of CPR skills compared to those who had never received it [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been highlighted that continuous training is required for nurses, especially when learning how to use sophisticated machines and skills in advanced procedures like defibrillation, and 12-lead ECG interpretation, while others require considerable repetition in training and clinical practice to keep up and performance improves when practicing relevant life support training courses. (Papi and Bahrami (2020); Tsegaye, et al (2015); Anderson (2019); Everett-Thomas, (2016). Torres (2019) and Ronda (2015), emphasize that the structure of the work environment provides conditions that can empower nurses, enabling them to be effective throughout all levels, reduce stress, promote nurse satisfaction, and financial costs or create a sense of powerlessness, which may influence patient and staff relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers adapted a four-part data collection tool developed by (Adenekan, et al, 2016;Mohamed, et al, 2019, Papi, et al, 2020 (Appendix 1). The first part addressed the demographic characteristics of the participants, followed by part two with 25 multiple choice knowledge-based questions.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation